Utilization of Colistin for Treatment of Multidrug-Resistant Pseudomonas aeruginosa - Deana M Sabuda; Kevin Laupland; Johann Pitout; Bruce Dalton; Harvey Rabin; Thomas Louie; John Conly (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Colistin is uncommonly used in clinical practice; however, the emergence of multidrug-resistant organisms has rekindled interest in this potentially toxic therapeutic option. The present study describes the authors’ experience with colistin in the management of patients who were infected with metallo-beta-lactamase (MBL)-producing Pseudomonas aeruginosa within the Calgary Health Region (Calgary, Alberta).